Analisis pengaruh sudut blade L terhadap performa turbin angin savonius-darrieus menggunakan computational fluida dynamic (CFD) - Bagus Kurniasandy (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
The Savonius-Darrieus turbine is a vertical axis wind turbine which has a shaft arranged perpendicularly parallel to the wind direction, so that it can receive wind from all directions. This research was conducted by modifying the L-shaped blade angle with variations in the angle of curvature of the turbine blade as many as 3 angle variations, namely 10⁰, 20⁰, and 30⁰ respectively, also simulating wind turbines using the CFD (Computational Fluid Dynamics) method with a variable wind speed of 2 m/s, 2.1 m/s, 2.4 m/s, and 2.5 m/s. From the graph of the relationship between wind speed and maximum velocity, and the graph of the relationship between wind speed and maximum pressure, it can be seen that a 30° blade angle wind turbine has the highest maximum velocity value with a value of 4,387 m/s^-1 at a wind speed of 2.5 m/s. A 20° blade angle wind turbine has the highest max velocity value with a value of 4,288 m/s-1 at a wind speed of 2.5 m/s. A 10° blade angle wind turbine has the highest maximum velocity value with a value of 4,280 m/s-1 at a wind speed of 2.5 m/s. The 30° blade angle wind turbine has the highest maximum pressure value with a value of 4.111 Pa at a wind speed of 2.5 m/s. A blade angle wind turbine of 20° has the highest maximum pressure value with a value of 4.795 Pa at a wind speed of 2.5 m/s. The 10° blade angle wind turbine has the highest maximum pressure value with a value of 4.105 Pa at a wind speed of 2.5 m/s.